Inversion in the temperature coefficient of the optical path length close to the glass transition temperature in tellurite glasses - Lima, S. M.; Andrade, L. H. C.; Falcao, E. A.; Steimacher, A.; Astrath, N. G. C.; Medina, A. N.; Baesso, M. L.; Oliveira, R. C. [UNESP]; Moraes, João Carlos Silos [UNESP]; Yukimitu, K. [UNESP]; Araujo, E. B. [UNESP] (American Institute of Physics (AIP), 2009)
In this study, thermal lens spectrometry was applied to determine the thermo-optical properties of fragile tellurite glasses as a function of temperature, close to the glass transition region. The results showed an inversion from positive to negative values in the temperature coefficient of the optical path length occurring after the glass transition temperature, which is the region where structural changes from the TeO(4) trigonal bipyramidal unit to a TeO(3) trigonal pyramid containing nonbridging oxygen take place. In addition, the thermal diffusivity values as a function of temperature exhibited behaviors that were related to thermodynamic and kinetic structural changes in the glass.
Keywords: glass transition; lithium compounds; optical glass; tellurium compounds; thermal diffusivity; thermal lensing; thermodynamic properties; titanium compounds